2007
DOI: 10.1016/j.ahj.2007.01.034
|View full text |Cite
|
Sign up to set email alerts
|

A community-wide perspective into changing trends in the utilization of diagnostic and interventional procedures in patients hospitalized with acute myocardial infarction

Abstract: Background-Limited data are available describing contemporary trends in the utilization of diagnostic and interventional procedures in patients hospitalized with acute myocardial infarction (AMI). The objectives of our population-based investigation were to examine long-term trends (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) in the utilization of cardiac catheterization, percutaneous coronary interventions (PCI), and coronary artery bypass graft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…Our results are in agreement with the findings from several prior studies and with our earlier publication [5,6,16]. In the National Registry of Myocardial Infarction, a decline in the use of thrombolytic therapy was observed in patients hospitalized with AMI at more than 1200 medical centers throughout the United States between 1990 and 1999 (34% to 21%); only minor increasesin the use of both PCI (7-10%) and CABG surgery (11-13%) were observed over this period [5].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are in agreement with the findings from several prior studies and with our earlier publication [5,6,16]. In the National Registry of Myocardial Infarction, a decline in the use of thrombolytic therapy was observed in patients hospitalized with AMI at more than 1200 medical centers throughout the United States between 1990 and 1999 (34% to 21%); only minor increasesin the use of both PCI (7-10%) and CABG surgery (11-13%) were observed over this period [5].…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with the results of numerous prior studies, which have shown the importance of rapid clot dissolution in patients with ST segment elevation MI [5,9,10]. Men were more likely to receive all procedures of interest relative to women, a finding that has been noted in several prior investigations [8,21], including our own [16]. In the National Inpatient Sample database, women underwent coronary angioplasty and stent placement at essentially similar rates with men over the period 1995 through 2001 [8]; women, however, were approximately 20% less likely to undergo coronary bypass surgery than men.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a study of Medicare patients, the rate of cardiac catheterization increased from 22 to 37 (per 1000 beneficiaries) between 1993 and 2001 16. A prior analysis from the Worcester Heart Attack Study also demonstrated that the utilization of cardiac catheterization increased more than three fold between 1986 and 2003 18. These findings demonstrate the widespread increase in the use of cardiac invasive procedures, many of which are associated with an EF measurement by ventriculography.…”
Section: Discussionmentioning
confidence: 90%